2016
DOI: 10.1007/s11242-016-0698-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Film Evaporation on Gas Transport Property in Fractured Wet Coal Seams

Abstract: Production data of coalbed methane have shown that coalbed may be wet for a long time after the completion of water flow and water-gas two-phase flow stages. In this period, water flows out in moisture vapor, but the water in matrix does not change so much. The moisture loss is mainly from the water film in fracture network. Experiments also observed that such a moisture loss has a profound impact on the storage and transport of coalbed methane. However, this impact has not been investigated so far. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…The presence of water films on porous mineral coated rocks has been previously reported in the literature (Nakagawa et al, 2000;Nishiyama and Yokoyama, 2013;Nishiyama et al, 2012;Teng et al, 2016;Tokunaga, 2011). In general, for hydrophobic surfaces a film of liquid should be swept away by the air flow and should not be retained.…”
Section: Observations In Cleat Drainage (Rie Channels)mentioning
confidence: 76%
“…The presence of water films on porous mineral coated rocks has been previously reported in the literature (Nakagawa et al, 2000;Nishiyama and Yokoyama, 2013;Nishiyama et al, 2012;Teng et al, 2016;Tokunaga, 2011). In general, for hydrophobic surfaces a film of liquid should be swept away by the air flow and should not be retained.…”
Section: Observations In Cleat Drainage (Rie Channels)mentioning
confidence: 76%
“…As water-wet surfaces are more likely to trap water in smaller pores (both micropores and micro-cleats), the result is that sections of the cleat network may not allow Darcy flow, as well as capillary effects that hinder gas diffusion from the matrix until the pressure difference has sufficiently decreased (Saghafi et al, 2014;Sakurovs and Lavrencic, 2011). Teng et al (2016) identified these restrictions in the cleats as a water film threshold pressure gradient (S) that could be ruptured if the differential gas pressure was sufficiently large. If the pressure was insufficient then the section of cleat becomes blocked and Darcy flow does not occur.…”
Section: Research Problemmentioning
confidence: 99%
“…Blockage B demonstrates a scenario where the gas pressure is insufficient to rupture S. Thus preferential flow pathways are created in the cleat network. Figure taken from Teng et al (2016 The focus on the micro-cleat, which can range from 6-260 μm (Dawson and Esterle, 2010;Kumar et al, 2011;Laubach et al, 1998;Mazumder et al, 2006;Solano-Acosta et al, 2007), was selected in this thesis for several reasons. 1) Surface wettability which may induce a residual liquid film will have a greater influence on the absolute flow permeability of micro-cleats compared to larger fractures.…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations